IMPLEMENTASI PEMBELAJARAN UNPLUGGED BERBASIS CODING PADA MATERI ‘GAYA DI SEKITAR KITA’ MATA PELAJARAN IPAS UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS 4 SDN 184 PEKANBARU - Dhini Ramadhani; Reva Anandita; Thania Revinza; Neni Hermita; Rifqa Gusmida Syahrun Barokah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by students' low problem-solving abilities in science learning. The aim of this study was to analyze the implementation of coding-based unplugged learning on the topic "Forces Around Us" in improving the problem-solving abilities of fourth-grade elementary school students. This study used a pre-experimental method with a one-group pretest-posttest design. Twenty fourth-grade students from SDN 184 Pekanbaru participated in the study. Data collection techniques used pretests and posttests to measure students' problem-solving abilities. The learning process was implemented through coding-based unplugged activities, including games, simulations, and developing problem-solving steps without using digital devices. The results showed a significant improvement, as evidenced by an average pretest score of 47.66, which increased to 96.66 in the posttest. The N-Gain value of 0.94 is in the high category. Thus, coding-based unplugged learning is effective in improving students' problem-solving abilities in science learning.